Remifentanil and dexmedetomidine as an alternative to regional analgesia in obstetrics - M. Aguilar-Montiel; O. Carrillo-Torres (Revista Médica del Hospital General de México, 2017)
Epidural analgesia for controlling pain in labour has been the gold standard over the past 2 decades as it is considered the least harmful technique for the newborn. In reality, however, it is not without risk. That said, there are few options for pain management in labour when epidural analgesia is contraindicated. A recent survey to investigate the use of alternatives showed remifentanil to be the first choice when using systemic analgesia intravenously, as short-acting opioids administered systemically relieve pain adequately without the need for epidural analgesia. Another safe option for providing obstetric analgesia is dexmedetomidine, a selective alpha-2 agonist that improves the quality of analgesia and reduces opioid requirements. Dexmedetomidine promotes stability and maintains uterine/placental homeostasis.